Strategies to improve stroke care services in low- and middle-income countries: a systematic review - Pandian, Jeyaraj; Jonas, Jost B. (Neuroepidemiology, 2017)
Background: The burden of stroke in low- and middle-income countries (LMICs) is large and increasing, challenging the already stretched health-care services. Aims and Objectives: To determine the quality of existing stroke-care services in LMICs and to highlight indigenous, inexpensive, evidence-based implementable strategies being used in stroke-care. Methods: A detailed literature search was undertaken using PubMed and Google scholar from January 1966 to October 2015 using a range of search terms. Of 921 publications, 373 papers were shortlisted and 31 articles on existing stroke-services were included. Results: We identified efficient models of ambulance transport and pre-notification. Stroke Units (SU) are available in some countries, but are relatively sparse and mostly provided by the private sector. Very few patients were thrombolysed; this could be increased with telemedicine and governmental subsidies. Adherence to secondary preventive drugs is affected by limited availability and affordability, emphasizing the importance of primary prevention. Training of paramedics, care-givers and nurses in post-stroke care is feasible. Conclusion: In this systematic review, we found several reports on evidence-based implementable stroke services in LMICs. Some strategies are economic, feasible and reproducible but remain untested. Data on their outcomes and sustainability is limited. Further research on implementation of locally and regionally adapted stroke-services and cost-effective secondary prevention programs should be a priority.
Published online: August 19, 2017
Gesehen am 11.06.2018